Pemanfaatan Kinect Dalam Prototype Aplikasi Media Pembelajaran Bagi Anak Berkebutuhan Khusus - Tri Sagirani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2015)
The use of Information Communication Technology (ICT) has become a fundamental need in supporting on educational process. ICT can supporting creativity and accuracy in the development of learning media. The need is not only for public schools but also for special educational needs (SEN), which is to prepare children with special needs to be able to live independently in the society. SEN is an educational unit that aims to help learners who bears a physical or mentally disabilities to be able to develop knowledge and skills. In this case, SEN group is the mild mental retardation with an IQ ranging from 50 to 70 and limitations in focus learning and activity, less creative and do not have the initiative, limitation to understand and use language. To support student with mental retardation, development of learning media are required in order to support teaching learning in SEN, by using input device such as mouse, keyboard, touch screen and Kinect. The learning media will be more interesting for SEN to provide user experience. Kinect is the one of input device in use, that is capable to provide the user experience more than the function other input devices, 67% in user interest and 83% in causing stimulation. This is because kinect has the ability to read body movements that can be used to train SEN.